(untitled) (Marketing Journal, 2026)
Abstract This article studies the theoretical, methodological and practical aspects of the effective use of marketing tools in ensuring the economic security of industrial enterprises in the conditions of an increasingly competitive environment. The study reveals the essence of the concept of economic security in its inextricable link with marketing activities, substantiates the importance of such tools as competitive intelligence, market monitoring, marketing information systems, pricing and product policy, segmentation and strategic analysis in enterprises. It also shows the possibilities of improving the quality of management decisions, early detection of external and internal threats, and rational use of resources through the systematic collection, processing and analysis of marketing information. Keywords: competitive intelligence, enterprises, economic and financial security of enterprises, risks, strategic stability.